ACSL1 Inhibits ALV-J Replication by IFN-Ⅰ Signaling and PI3K/Akt Pathway - Zhang, Qihong; Xie, Tingting; Mo, Guodong; Zhang, Zihao; Lin, Ling; Zhang, Xiquan (Frontiers in Immunology, 2021)
J subgroup avian leukosis virus (ALV-J) infection causes serious immunosuppression problems, leading to hematopoietic malignancy tumors in chicken. It has been demonstrated that interferon-stimulated genes (ISGs) could limit ALV-J replication, nevertheless, the underlying mechanisms remain obscure. Here, we demonstrate that Long-chain Acyl-CoA synthetase 1 (ACSL1) is an interferon (IFN)-stimulated gene that specifically restricts the replication of ALV-J due to the higher IFN-Ⅰ production. More importantly, ACSL1 induces primary monocyte-derived macrophages (MDMs) to pro-inflammatory phenotypic states during ALV-J infection and ACSL1 mediates apoptosis through the PI3K/Akt signaling pathway in ALV-J-infected primary monocyte-derived macrophages (MDMs). Overall, these results provide evidence that ACSL1 contributes to the antiviral response against ALV-J.